REPRESENTATION OF AFRICAN AMERICAN IDENTITY AND SOCIAL CRITICISM IN THE MUSIC VIDEO "ALL THE STARS" BY KENDRICK LAMAR AND SZA: A BARTHESIAN SEMIOTIC ANALYSIS - Argi Puji Widodo; Tyas Alhim Mubarok; Widiarini Widiarini; Istina Atul Makrifah (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
Hip-hop music videos function as semiotic texts that encode cultural identity and social critique, making them significant objects of study in media and cultural analysis. Prior research on hip-hop visuals has largely focused on lyrical content, genre history, or the political function of individual artists, with comparatively few studies applying a layered semiotic framework, specifically Barthes's model of denotation, connotation, and myth, to a single music video that combines Afrofuturist visual language with explicit social commentary. Within this body of work, the particular combination found in "All the Stars," namely the fusion of African royal imagery, contemporary street aesthetics, and direct references to poverty and historical trauma, has not previously been examined through this specific theoretical lens. This study analyzes how African American identity and social critique are represented in Kendrick Lamar and SZA's music video "All the Stars" (2018), released alongside the Black Panther soundtrack. Using a qualitative descriptive design grounded in Barthes's semiotic theory, the analysis draws on 18 purposively selected scenes and their corresponding lyric segments, chosen for their visual density and thematic relevance to identity and critique across the video. The selected scenes were interpreted as constructing an affirmative representation of African American identity through Afrofuturist visual codes, and as articulating a social critique of poverty and historical trauma tied to the African diaspora's collective memory. These findings suggest that hip hop music videos can operate as a site where cultural meaning and social commentary are worked through visual form, offering one case study within the wider study of popular audiovisual media and cultural representation.